A CROSS-SECTIONAL OBSERVATIONAL STUDY REGARDING KNOWLEDGE, ATTITUDE, AND PRACTICE OF CONTRACEPTION AMONG ELIGIBLE COUPLES RESIDING IN THE FIELD PRACTICE AREA ASSOCIATED WITH TERTIARY CARE CENTER - PREETI; PRATAP SINGH, JASPINDER (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study were to observe the knowledge, attitude, and practice among the eligible couples in the area of study. Methods: A population-based cross-sectional study was done in the field practice area of Postpartum Unit, Department of Obstetrics and Gynaecology, Rajindra Hospital, Patiala. Institutional Ethical Committee approval was taken. A structured questionnaire was made and validated. The knowledge, attitude, and practice related to contraceptives were thoroughly asked by face-to-face interviews with the eligible couples (15–49 years) with the help of a pre-validated and pre-tested questionnaire. The sample size for frequency in a population is 350. Results: The majority of the population 181 (51.7%), belongs to the age group of 30–39 years, followed by 114 (32.6%) in the age group of 20– 29 years and 52 (14.8%) in 40–49 years. 298 (85.14%) couples had knowledge regarding contraception and family planning. The majority of the population in the area of study had opted for permanent sterilization methods that included tubectomy in 103 (29.4%) cases, followed by vasectomy in 81 (23.1%) cases. The majority of couples, 25 (29.4%), had a fear of the side effects of the contraceptive, followed by feeling ashamed to buy 19 (22.3%). Of 298 (85.14%) couples had knowledge regarding contraception and family planning, and among those were literate. While 52 (14.86%) cases did not have knowledge of contraception, in which 20 (42.6%) were illiterate. Conclusion: We can conclude that awareness about newer contraceptive methods is still lacking and needs to be increased at the community level as well as by the health-care workers by formulation of new policies by the government.